Pembuatan Sistem Informasi Inventaris Politeknik Kampar Berbasis Web Menggunakan PHP dan MySQL dengan Framework CodeIgniter - Fitri (Jurnal Sains dan Ilmu Terapan, 2021)
The data inventory collection carried out at the Politeknik Kampar returned to the manual. It is rated less effective because the data collection is still less accurate. In addition, manual logging is also assessed as less efficient in data processing because it tends to be slow, requiring a long time and waste of cost. . In the process of the design using the Unified Modeling Language (UML) method, as well as the implementation stage is done using the PHP programming language, phpMyAdmin manages the databases in MySQL and the CodeIgniter framework. This WEB-based Politeknik Kampar inventory information System has been successfully created. WEB-based Kampar Polytechnic inventory information System has been able to assist in saving waste time and cost.